Предмет: Математика,
автор: galieva19991
2(5x-4у+1)-3(3х+3у+1)
Ответы
Автор ответа:
0
2(5x-4у+1)-3(3х+3у+1)Раскроем скобки: 10х-8у+2-9х-9у-3
Приводим подобные, считаем: 10х-9х = х
-8у-9у = -17у
2-3 = -1
Получаем уравнение: х-17у-1
Приводим подобные, считаем: 10х-9х = х
-8у-9у = -17у
2-3 = -1
Получаем уравнение: х-17у-1
Похожие вопросы
Предмет: Русский язык,
автор: tane4kafox4
Предмет: Окружающий мир,
автор: egorshipp
Предмет: Математика,
автор: nastakozyr28
Предмет: Химия,
автор: LizaGrin59
Предмет: Биология,
автор: kazka1972